2015
DOI: 10.2119/molmed.2014.00238
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of mTOR Activity with Torin2 Potentiates Anticancer Effects of Cisplatin in Epithelial Ovarian Cancer

Abstract: Mammalian target of rapamycin (mTOR) and phosphatidylinositol 3-kinase (PI3K) are two key components of PI3K/Akt/mTOR signaling pathway. Dysregulation of these pathways have been found in many cancers, including epithelial ovarian cancer (EOC), however, the role of mTOR has not been fully elucidated in Middle Eastern EOC. Therefore, we investigated the activation of mTOR complexes (mTORC1 and mTORC2) in a cohort of 156 EOC from Saudi Arabia by immunohistochemistry in a tissue microarray format. mTORC1 and mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Another study conducted by Hussein et al, where a second-generation mTor inhibitor, Torin2 was tested, resulted in the inhibition of tumor cell viability and induction of apoptosis in epithelial ovarian cancer. In addition, this study found that combination in vivo of Torin2 and cisplatin synergistically inhibited tumor growth in nude mice, confirming the hypothesis that mTor inhibitors might serve as single agent therapies as well as in combination with other treatment options, acting either as synergic agents or sensitizing ones 61 , 64 . In this scenario, it was also recently shown that the combination of PIK3 inhibitor BKM120 with PARP inhibitor olaparib resulted in reduced proliferation, survival and invasion in different ovarian cancer cell lines harboring PIK3CA mutations and in a significantly decreased BRCA1 expression in SKOV3 ovarian cancer cells 65 .…”
Section: Mtor Inhibitorssupporting
confidence: 78%
“…Another study conducted by Hussein et al, where a second-generation mTor inhibitor, Torin2 was tested, resulted in the inhibition of tumor cell viability and induction of apoptosis in epithelial ovarian cancer. In addition, this study found that combination in vivo of Torin2 and cisplatin synergistically inhibited tumor growth in nude mice, confirming the hypothesis that mTor inhibitors might serve as single agent therapies as well as in combination with other treatment options, acting either as synergic agents or sensitizing ones 61 , 64 . In this scenario, it was also recently shown that the combination of PIK3 inhibitor BKM120 with PARP inhibitor olaparib resulted in reduced proliferation, survival and invasion in different ovarian cancer cell lines harboring PIK3CA mutations and in a significantly decreased BRCA1 expression in SKOV3 ovarian cancer cells 65 .…”
Section: Mtor Inhibitorssupporting
confidence: 78%
“…This decision allowed us to distinguish effects related to DNA repair from autophagic responses (19). Moreover, a recently reported study demonstrated that at sublethal doses, Torin2 synergizes with cisplatin to inhibit the growth of ovarian carcinoma cell lines (69), suggesting that low doses of Torin2 are capable of enhancing the DNA damage response when combined with existing radiotherapeutic agents routinely used in clinical settings. Importantly, Torin2 was also reported to have a good safety profile in mouse models, suggesting that the drug may not have deleterious effects on normal tissues (16).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies also revealed that in combination of Torin2 and cisplatin, tumor growth in nude mice was synergistically inhibited. Overall, such studies highlight the importance and potential of targeting the mTOR survival pathway, suggesting that co-treatment of cisplatin and mTOR inhibitors, such as Torin2, may be beneficial for the management of EOC and various other resistant cancers [ 64 ].…”
Section: Main Textmentioning
confidence: 99%